Factors That Determine the Likelihood of Giving Birth to the First Child within 10 Months after Marriage - Abdul-Karim Iddrisu; Francis Kwame Bukari; Kwaku Opoku-Ameyaw; Gabriel Oppong Afriyie; Kassim Tawiah (Hindawi Limited, 2020)
Background. One of the major aims of marriage is to procreate or give birth to a child. Childbirth is so crucial in marriage that it often determines the happiness of the couple. Too much delay in childbirth after marriage or the likelihood that one cannot give birth after marriage can lead to divorce. However, causes of delay in childbirth are often difficult to detect by both the Gynaecologist and the couple involved. This makes proposing solutions to issues related to childbirth usually unsuccessful. Methods. It is against this background that we conducted this study to identify factors that determine childbirth within 10 months or after 10 months of marriage (birth length) among women in Ghana. This was achieved by using a logistic regression model for the dichotomous birth length variable, adjusting for risk factors/predictors of birth length. The data used for the study were obtained from the 2014 Ghana Demographic and Health Survey, consisting 6,525 complete cases with 18 predictor variables. Statistical analyses were carried out using STATA version 14.1. Results. The results show that respondents who have ever terminated pregnancy are more likely (OR=0.178, 95%CI=0.044, 0.312) to deliver after 10 months, wives whose husbands have higher education are less likely (OR=‐0.162, 95%CI=‐0.236, ‐0.088) to give birth after 10 months of marriage, wives who reported that beating is justified if she goes out without her husband's notice are more likely (OR=0.466, 95%CI=0.305, 0.628) to give birth after 10 months, wives who reported that beating is justified if she neglects the child are more likely (OR=‐0.305, 95%CI=‐0.461, ‐0.149) to give birth within 10 months, and wives who reported that beating is justified when she argues with her husband are less likely (OR=‐0.301, 95%CI=‐0.451, ‐0.152) to give birth after 10 months of marriage. Every unit increase in the age of the respondent at marriage increases the likelihood of giving birth after 10 months of marriage, and a unit increase in the age of the respondent at first sex decreases the likelihood of giving birth after 10 months in marriage. Conclusions. For conception within 1 month of marriage, wives and husbands should/are encouraged to have frequent sex, any negative social behaviour or policies must be discouraged, experts' advice on contraceptive use must be sought, and women are encouraged to desist from termination of pregnancy at any time of their life. Husbands should openly express their desire and love for their children since this increases the likelihood of wives' desire to give birth. This leads to frequent sex, which then reduces conception time, and hence childbirth within the shortest possible time.